Sosialisasi Dan Pelatihan Penggunaan Aplikasi Buku Warung Bagi Para Pelaku UMKM Di Binong - Yohana Yohana; Chandra Puspa Arum Pertiwi; Heri Juliadi; Kurniati Jihan Fadhilah; Nadia Wulandari; Ratu Gunawan; Yuliana Sari (Institut Nalanda, 2024)
Binong, an urban village in Tangerang Regency, Banten, is dominated by Micro, Small and Medium Enterprises (MSMEs), especially in Binong Village. MSMEs play a crucial role in economic growth and economic resilience. However, they face obstacles, including low education and lack of understanding of technology. This research highlights the improvement of accounting knowledge of Binong MSME players through the Warung Book Application. The community service program was implemented using socialization, training, and mentoring methods. The results show that before the program, MSME players had minimal knowledge of the Buku Warung App, but after the training, they were able to utilize it for daily bookkeeping efficiently. The Buku Warung application allows MSMEs to record finances easily and practically. This program is expected to improve the quality of financial management, support business growth, and have a positive impact on the local economy.